2022
DOI: 10.3233/adr-220061
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Mechanism Between the HSV-1 Glycoprotein B and the Antimicrobial Peptide Amyloid-β

Abstract: Background: Unravelling the mystery of Alzheimer’s disease (AD) requires urgent resolution given the worldwide increase of the aging population. There is a growing concern that the current leading AD hypothesis, the amyloid cascade hypothesis, does not stand up to validation with respect to emerging new data. Indeed, several paradoxes are being discussed in the literature, for instance, both the deposition of the amyloid-β peptide (Aβ) and the intracellular neurofibrillary tangles could occur within the brain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We envisage that our 439 methodology will be useful to understand not only pro-440 tein structures but also protein interactions in the context 441 of disease models. For instance, this could be applied 442 to Alzheimer's Disease where it has been found that 443 amyloid-beta peptides have anti-microbial role and may 444 interact with glyco-proteins of various pathogens [44][45][46][47][48] . 445 Moreover, we envisage that extensions of our proposed 446 methodology will in the long-term contribute to the am-447 bitious goal of predicting the 3D structure-functional 448 relationship of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We envisage that our 439 methodology will be useful to understand not only pro-440 tein structures but also protein interactions in the context 441 of disease models. For instance, this could be applied 442 to Alzheimer's Disease where it has been found that 443 amyloid-beta peptides have anti-microbial role and may 444 interact with glyco-proteins of various pathogens [44][45][46][47][48] . 445 Moreover, we envisage that extensions of our proposed 446 methodology will in the long-term contribute to the am-447 bitious goal of predicting the 3D structure-functional 448 relationship of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HSV-1 (which will be elaborated on more throughout this review) has genetic factors, such as the apolipoprotein E isoform 4, APOE ε4, that assist HSV-1 invasion and latency establishment in the brain of APOE ε4 knockout mice [ 25 ]. HSV-1 also participates in the induction of Aβ and tau pathogenesis through virion particles encouraging the oligomerization and fibrilization of Aβ through physical interaction with the virus’ surface glycoprotein B along with multiple tau phosphorylation sites identified with HSV-1 infection in neuronal cells [ 26 , 27 , 28 ]. These approaches to this viral hypothesis, coupled with advancements in molecular and cellular biology, have encouraged researchers to probe deeper into the possible precise mechanisms underlying the viral hypothesis in AD.…”
Section: Historical Perspectives On Viral Links To Admentioning
confidence: 99%
“…The colocalization of Aβ plaques and viral proteins (e.g., glycoprotein B) is observed via immunostaining with antibodies against HSV-1 and Aβ ( Eimer et al, 2018b ; Ezzat et al, 2019 ). To exert its antiviral activity, Aβ deposits on HSV-1 virion particles such that HSV-1 induces the oligomerization and fibrilization of Aβ through physical interaction with its surface glycoprotein B, a ligand mediating HSV-1 entry ( Bourgade et al, 2022 ; Yirün et al, 2023 ). Recently, the mechanistic connections between HSV-1 and Aβ pathology have been extensively studied, and these findings collectively support a causative role of HSV-1 in the neurodegeneration of AD.…”
Section: Hsv-1 Induces Amyloid β and Tau Pathogenesismentioning
confidence: 99%